Surface Energy of Insoluble Organic Matter Simulant: Evaluation Based on Adhesive Force Measured by Centrifugal and Impact Separation Methods - Yuuya Nagaashi; Yoshihiro Furukawa; Akiko M. Nakamura (The Planetary Science Journal)
In protoplanetary disks, organic mantle is regarded as promoting the collisional sticking of rocky dust grains. However, the surface energy, which is one of the primary factors determining collisional sticking, has not been well quantified. Here, we evaluated it by measuring the adhesive forces of synthetic insoluble organic matter, which is a realistic, chemically synthesized simulant of the organic matter found in meteorites, comets, and interplanetary dust particles. The simulant was prepared by repeated decantation of the reaction products of small reactive molecules, which are observed abundantly in protoplanetary disks. The adhesive force was measured at room temperature using both centrifugal and impact separation methods. For the latter, we developed a new apparatus that may enable measurements under varied conditions in the future as the organic matter is sensitive to temperature. We demonstrated that the measurements obtained with the new apparatus worked well as they closely matched those obtained using the centrifugal method. The measurements show that the surface energy of the simulant is ∼10 mJ m ^−2 , which is comparable to or even lower than that of silica, depending on disk conditions. Therefore, assuming that the simulant is similar to protoplanetary organic matter, the surface energy of the organic matter would not promote the collisional sticking of rocky dust grains. Other factors, such as the viscosity of organic matter, the role of water-soluble organic matter, and the environmental conditions in protoplanetary disks, may help us better assess the true effects of organic matter on collisional sticking.